The Association Between Disgust Sensitivity and Negative Attitudes Toward Homosexuality: The Mediating Role of Moral Foundations - Wang, Ruile; Yang, Qi; Huang, Peng; Sai, Liyang; Gong, Yue (Frontiers in Psychology, 2019)
Previous studies have found that “disgust-sensitive” individuals have negative attitudes toward gay and lesbian people, but the underlying mechanisms for such attitudes remain unclear. Based on moral foundations theory, the current paper assumes that the relationship between disgust sensitivity and attitudes toward homosexuality are mediated by moral foundations. In order to test this assumption, the current authors examined the questionnaire answers from a total of 452 Chinese undergraduates who participated in this study. The results showed that disgust sensitivity was positively correlated with negative attitudes toward homosexuality, and positively correlated with moral concerns in five domains (care, fairness, loyalty, authority and sanctity). Authority and sanctity were both associated with attitudes toward homosexuality, while only sanctity mediated the relationship between disgust sensitivity and attitudes toward homosexuality. Overall, the results suggest that considering moral foundations (especially sanctity) may lend more insight to the associations between disgust sensitivity and negative attitudes toward gay and lesbian people.